2018
DOI: 10.1002/app.46397
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal conductivity of PLA‐based nanocomposites by incorporation of graphite nanoplatelets functionalized by tannic acid

Abstract: Enhancing thermal conductivity of polymeric nanocomposites remains a great challenge because of the poor compatibility between nanofillers and the polymeric matrix and the aggregation effect of nanofillers. We report the enhanced thermal conductivity of poly(lactic acid) (PLA)-based nanocomposites by incorporation of graphite nanoplatelets functionalized by tannic acid. Graphite nanoplatelets (GNPs) were noncovalently functionalized with tannic acid (TA) by van der Waals forces and p-p interaction without pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
(57 reference statements)
0
9
1
Order By: Relevance
“…As expected, the addition of GNP to the polymer matrix turns out to significantly influence the thermal conductivity, with values in the range of 0.78–0.94 W m –1 K –1 . These values are significantly higher compared to results previously reported in the literature for both graphite 32 and graphite nanoplatelets 34 at the same weight percent used in this work. Most interestingly, the thermal conductivity of the nanocomposites strongly depends on the type of initiator, with significantly enhanced thermal conductivities in the presence of stereocomplexed PLLA.…”
Section: Results and Discussioncontrasting
confidence: 76%
“…As expected, the addition of GNP to the polymer matrix turns out to significantly influence the thermal conductivity, with values in the range of 0.78–0.94 W m –1 K –1 . These values are significantly higher compared to results previously reported in the literature for both graphite 32 and graphite nanoplatelets 34 at the same weight percent used in this work. Most interestingly, the thermal conductivity of the nanocomposites strongly depends on the type of initiator, with significantly enhanced thermal conductivities in the presence of stereocomplexed PLLA.…”
Section: Results and Discussioncontrasting
confidence: 76%
“…The enhancement in intensities was due to the introduction of TA on the one hand and the exfoliation of a few graphene layers from graphite during the preparation process on the other hand. The results showed that the characteristic peaks of TA can be observed also at the TA-G, which suggested that TA was successfully functionalized G by the π–π conjugative effect [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…TC of PLA-based composites is linearly positively correlated with material density, with pure PLA having low TC for its density and glass fibre-reinforced plastics having high TC relative to density (Tagaki et al, 2002) [35]. The TC of pure PLA is low (between 0.13 and 0.2 W/(m•K)), but very effectively enhanced by the addition of fine carboniferous materials like graphene (Lin et al, 2018) [36]. Chiang et al, (2013) [37] recorded an increase in the TC of epoxy resin from 0.17 W/(m•K) to 0.23 with the addition of 2% BC powder, and a study by Tagaki et al, (2002) [35] showed how adding 60% w/w bamboo fibre to PLA increased its solid phase TC from 0.2 W/(m•K) to 0.34 W/(m•K), with modelling indicating the TC of solid bamboo fibre substrate is greater than 0.34 W/(m•K).…”
Section: Discussion-theoretical Model For Flame-retardant Mechanismmentioning
confidence: 99%